Solitary bone cyst of posterior maxilla: A rare presentation - Sneha P Patil; Sonia J Sodhi; Sunil S Mishra; Syeda Shadab Farha (Wolters Kluwer Medknow Publications, 2019)
Solitary bone cyst (SBC) is an uncommon, nonneoplastic osseous lesion that mainly affects metaphysis of long bones and rarely presents in jaws. Due to the lack of true epithelial lining, it is considered as a pseudocyst. It is generally asymptomatic and often discovered incidentally during routine radiographic examination as well-defined unilocular or multilocular radiolucent lesion in the posterior mandible mainly in the first two decades of life. Here, we report a very rare case of a 15-year-old female patient having a lesion in the posterior maxilla with clinical, radiological, and histopathological presentations of SBC.